Bark Fibre Length of Some Indian Tropical Trees - Brat, K. M.; Trulasidas, P. K.; Easa, P. S. (Indian Forester, 1989)
Data for minimum, mean and maximum bark fibre length of 30 Indian timbers are reported. Shortest bark fibres with a mean of 0.86 mm, were found in Mimusops elengi and the longest, with a mean of 4.18 mm. in Ficus hispida. Of the 30 species studied, four species had short-fibre bark (mean value of < 1 mm), three species long-fibre bark (mean value of > 2 mm) while the mojority bad the bark with medium-size fibres (mean value of 1-2 mm). Bark-fibre length was, by and large, greater than wood fibre length. Two species, viz. Bischofia javanica and Dillenia pentagyna did not show the presence of fibres in the bark.